WORKING STANDARD OF BRIGHTNESS BASED ON INTEGRATING SPHERE WITH DIFFUSER - Mikheienko, L. A.; Puhina, M. O. (Visnyk of Vinnytsia Politechnical Institute, 2015)
The research deals with radiometric and metrological characteristics of the working standard of brightness and power spectral density of energy brightness based on diffuse emitter, which consists of integrating sphere and the lens of milk or frosted glass, which is set in the original aperture. The influence of the main components of the final standard brightness index (including environment inside the integrating sphere) is analyzed. A metrological analysis revealed the dependence of relative error of setting the brightness of the original error and the error output aperture brightness depending on the instability of the main elements of the standard brightness. The recommendations on the design of standard of brightness are developed.